A new Schistura from an upper Mekong affluent in Yunnan (Teleostei: Nemacheilidae) - Endruweit, Marco (Zootaxa, 2017)
Schistura stala, new species, is described from the Mekong drainage in Dali, Yunnan Province, China. The new species is readily distinguished from congeners in the upper Mekong and adjacent drainages by having the caudal-fin bar reduced, stretching over the median ⅓ of the fin base. The species can be further diagnosed by a deep body; a short caudal fin, head and pelvic fin; 38 vertebrae modally; 9–12 faint irregular flank bars, that are often anastomotic or dissolved; and few scales scattered on the anterior part of the body.